Ultrafast all-optical control of the magnetization in magnetic dielectrics - Kirilyuk, A.; Kimel, A.; Pisarev, R.V.; Hansteen, F.; Rasing, T. (Физика низких температур, 2006)
The purpose of this review is to summarize the recent progress on laser-induced magnetization
dynamics in magnetic dielectrics. Due to the slow phonon–magnon interaction in these materials,
direct thermal effects of the laser excitation can only be seen on the time scale of almost a nanosecond
and thus are clearly distinguished from the ultrafast nonthermal effects. However, via the
crystal field, laser pulses are shown to indirectly modify the magnetic anisotropy in rare-earth
orthoferrites and lead to the spin reorientation within a few picoseconds. More interesting, however,
are the direct nonthermal effects of light on spin systems. We demonstrate coherent optical
control of the magnetization in ferrimagnetic garnet films on a femtosecond time scale through a
combination of two different ultrafast and nonthermal photomagnetic effects and by employing
multiple pump pulses. Linearly polarized laser pulses are shown to create a long-lived modification
of the magnetocrystalline anisotropy via optically induced electron transfer between nonequivalent
ion sites. In addition, circularly polarized pulses are shown to act as strong transient magnetic
field pulses originating from the nonabsorptive inverse Faraday effect. An all-optical scheme of excitation
and detection of different antiferromagnetic resonance modes with frequencies of up to
500 GHz will be discussed as well. The reported effects open new and exciting possibilities for
ultrafast manipulation of spins by light, and provide new insight into the physics of magnetism on
ultrafast time scales.